Dealing with chemical safety - Safetycare Australia Pty. Ltd. ([S.l.] : Safetycare Australia, 1989)
Described on terms of chemicals and explain a safe way of handling and using all chemicals
Accompanied by 1 trainer's manual
Keywords: Chemical industry -- Safety measures; Chemical laboratories -- Safety measures